Comparing the effectiveness of mindfulness-based parenthood intervention for mothers and self compassion intervention for girls on resilience of teenage girls having parent-child conflict in COVID-19 Pandemic - Mehrabi koshki , Malihe; Keshavarzi Arshadi, Farnaz; Hassani , Fariba; Kouchak Entezar, Roya (Applied Family Therapy Journal (AFTJ), 2023)
Aim: The present study is conducted with the aim of comparing the effectiveness of mindfulness-based parenthood intervention for mothers and self-compassion intervention for girls on resilience of teenage girls that have parent-child conflict. Method: The research method was quasi-experimental with a pre-test post-test design. It also had control group and follow-up. The statistical population of the study consisted of 14 and 15 years old teenage girls who were studying in public schools in district 14 of Tehran, in the school year 2021-22 and their mothers. The sample of the study was 34 students who were selected by purposive sampling method and randomly divided into three groups. The first group were 10 of the student’s mothers who received mindfulness-based parenthood intervention (Bogels & Restifo, 2014) and the second group consisted of 12 students who received self-compassion intervention (Gilbert, 2010). Besides, the control group consisted of 12 students who didn’t receive any intervention. Data:were collected with resilience scale (Conner & Davidson, 2003). Results: The outcomes of the analysis of mixvariance demonstrated that mindfulness-based parenthood intervention for mothers and self-compassion intervention for girls were significantly effective on resilience, compared to the control group (F=19/63, P=0/001). and there were no significant differences between the effectiveness of the two methods and the effects of intervention over time remained constant (p≤0.001). Conclusion: Therefore, these interventions can be used in school counseling environments so as to increase resilience, improve relationships, for adolescents who have conflict with their parents.